Sustainable PPPs: A comparative approach for road infrastructure - Villalba-Romero, Felix; Liyanage, Champika; Roumboutsos, Athena (Elsevier, 2015)
The construction of road infrastructure is often a difficult issue for many countries. While many developing countries do not have public funds available, other developed countries experience public budget restrictions that limit the country's infrastructure development. Public Private Partnership (PPP) appears to be an adequate mechanism for empowering those countries, both developing and developed, to bring together the public and the private sector and to find efficient ways for public funding and public services provision Public Private Partnership is not however a panacea, instead mean a limited approach that is valid for feasible projects, and given the current economic context it may be the only solution for road provision in some cases. Moreover, affordability limitations and viability conditions become key factors to make projects financially sustainable. From a case study analysis carried out on many projects in Europe, COST Action TU1001, Public Private Partnerships in Transport: Trends & Theory P3T3 , it may show evidence of key factors (or key performance indicators) that might drive to success or failure. The idea of this paper, therefore, is to identify the elements for assessing sustainability in transport projects against these KPIs. A comparative analysis using 04 case studies (road projects) from Greece, Portugal, Spain and UK were chosen to achieve the main purpose of the paper. The findings and implications may be of interest at the time of implementing and designing a sustainable and efficient policy for road infrastructure. These results may be considered in many countries which are preparing a master program of national roads.
Keywords: Carreteras - Diseño y construcción; Key performance indicators (KPIs); Critical Success Factors (CSFs); Toll roads